2018
DOI: 10.1007/s11748-018-0936-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the analgesic effects of modified continuous intercostal block and paravertebral block under surgeon’s direct vision after video-assisted thoracic surgery: a randomized clinical trial

Abstract: Our results could not clearly establish noninferiority of ICB to PVB. Improvements in ICB may be necessary for it to be used as an alternative method to PVB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 27 publications
0
43
0
3
Order By: Relevance
“…In addition, two studies which are not RCTs were also excluded. Finally, the remaining 9 studies [13][14][15][16][17][18][19][20][21] were included in our systematic review and meta-analysis. The strategy of the research and the process of the selection were shown in the flow diagram of…”
Section: Identification Of Eligible Studies Characteristics Of the Stmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, two studies which are not RCTs were also excluded. Finally, the remaining 9 studies [13][14][15][16][17][18][19][20][21] were included in our systematic review and meta-analysis. The strategy of the research and the process of the selection were shown in the flow diagram of…”
Section: Identification Of Eligible Studies Characteristics Of the Stmentioning
confidence: 99%
“…Although there was no heterogeneity in above analysis, we still performed the subgroup analysis to investigate that whether the VAS at rest at 48h was influenced by the use of opioid drug or NSAIDs. After excluding the study using NSAIDs Kadomatsu (2018) [17], there was also no heterogeneity in the subgroup (I 2 = 0%, heterogeneity P = 0.44) and there was no significant difference between Opioid drug and NSAIDs and INB (Std. MD = -0.05; 95% CI = -0.20 to 0.11; P = 0.56) (Fig 15).…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…La inserci on de catéter paravertebral por parte del cirujano durante el procedimiento (BPV-C) se realiz o en 18 estudios, 11,[16][17][18][34][35][36][37][38][39][40][41][42][43][44][45][46][47] siendo esta la técnica de BPV más representativa, al ser evaluada en el 46 % de los estudios incluidos en la revisi on. Este tipo de abordaje fue el que mayor variaci on tuvo a través de los estudios incluidos, dado que la técnica de punci on cambi o de manera sustancial de acuerdo con el grado de visualizaci on quir urgica del cirujano durante el procedimiento quir urgico; adicionalmente, los momentos del bloqueo fueron altamente inconsistentes, dado que en algunos estudios este se realiz o al inicio de la cirugía, en otros antes de la toracotomía (mediante toracoscopia previa para su colocaci on) 25,26,28,34,48 y en otros al finalizar el procedimiento quir urgico.…”
Section: Características De Los Estudiosunclassified